ANTECEDENTS AND CONSEQUENCES OF UNEMPLOYMENT: EMPIRICAL EVIDENCE FROM UAE - Marri, Maryam Taresh Saif Suhail Al; Majid, Abdul Halim B Abdul (CENTRAL ASIA AND THE CAUCASUS, 2021)
Unemployment measures how many laborers in a specific country are educated and skilful but unable to find a job either in the private or public sector. Labor keeps waiting to get a public position, and unemployment in UAE keeps growing every year. An unemployment rate of 25 percent would mean that 25 percent of employees are willing to work but can’t find work, and every year, the burden keeps rising on the UAE government to generate jobs for their locals. Some level of unemployment is inevitable in any country, but high unemployment could slow down economic growth. Unemployment could be expensive as any country needs to balance technical and non-technical graduates and their job placements or else provide them financial schemes to start their businesses. The causes of high unemployment rates can project unscrupulous strategies and policies that will even make the scenario worse. Now the question is how to reverse the trend and control growing unemployment. This paper investigates the interrelationship among major antecedents of unemployment, such as weak HRM policies and practices, consequences of unemployment in the UAE, and possible future solutions for making the UAE a country full of job opportunities. This paper will also ponder the government agencies' perspectives and understand how to solve unemployment problems. This conceptualization helps compare and categorize emerging themes in understanding current unemployment problems in UAE.